Innovative Analog Processing-Based Approach for Power-Efficient Wireless Transceivers - Mir Mahdi Safari; Jafar Pourrostam; Behzad Mozaffari Tazehkand (IEEE Access)
As the demand for energy-efficient, affordable, and fast processors increases, analog signal processing (ASP) techniques emerge as promising solutions. Embracing innovative transmission and reception methods becomes vital in addressing evolving challenges and demands as technology advances. In this paper, we propose a power-efficient direct analog demodulation method for M-QAM constellations. We study the general structure of the square QAM constellation and also propose a general direct analog demodulation structure for cross QAM constellations. Additionally, this paper investigates a novel approach for implementing ADC-less joint analog demodulation and decoding (JADD) in wide-band multi-gigabit-per-second applications. On the transmitter side, new processes based on multi-carrier transmission are employed to separately transmit the message and modified parity bits. The message bits are divided into block and non-block bits. Both the message and modified parity bits are demodulated analogously, and the joint analog demodulation and decoder are applied. Our analysis and simulations show that the proposed JADD model improves system performance in terms of bit error rate (BER) while achieving a $12× $ power saving. Moreover, our proposed analog demodulation scheme can achieve the same error performance as its digital counterpart with more than $28× $ power savings.